Mechanical behavior of reservoir bank slope–pile–sheet structures under reservoir operation: Field monitoring and numerical simulation analysis - Zhiwei Cai; Tongqing Wu; Lei Nie; Yue Wu; Zhao Xiang; Zhijie Yang; Nianchun Xu; Fei Qi (PLoS ONE, 2026)
Long-term fluctuations in reservoir water levels can lead to the deterioration of bank slope materials, representing a key trigger of instability. This study investigated the behavior of a slope–pile–sheet support structure at a site in Chongqing’s “Two Rivers and Four Banks” area through an integrated program of field monitoring and numerical simulation. The results demonstrated a strong correlation between slope displacement/settlement and water-level fluctuations, exhibiting a characteristic three-stage process. Rapid drawdown triggered substantial horizontal displacement with a one-month response lag, while settlement primarily occurred during water-level rise. Earth pressure behind the piles exhibited a non-linear R-shaped distribution, with a delayed response in shallow layers and a pronounced local pressure drop at 8 m depth indicative of seepage erosion. The pile bending moment showed a distinct S-shaped profile, with a maximum positive moment (1978.44 kN·m) at the rock-soil interface (13 m) and a negative moment zone below 21 m. The bending moment response also exhibited a one-month lag and was particularly sensitive to rapid drawdown. The identified contraflexure point at 21 m depth provides a basis for pile length optimization. The close agreement between numerical simulations and field data validates the strong hydro-mechanical coupling in the system. This research provides theoretical and practical support for the design and optimization of similar support structures in reservoir bank environments.